2023
DOI: 10.3390/w15234098
|View full text |Cite
|
Sign up to set email alerts
|

Water and Salinity Variation along the Soil Profile and Groundwater Dynamics of a Fallow Cropland System in the Hetao Irrigation District, China

Cong Hou,
Qingfeng Miao,
Haibin Shi
et al.

Abstract: Managing soil salinity has always been a difficult problem for agriculture. Balancing water and salt while maintaining crop quality and yield is a key issue for agricultural sustainability. The Hetao lrrigation District in China has a complex mix of cultivated and uncultivated land which plays a crucial role in soil salinization processes. To investigate the dynamic properties of soil moisture and salinity, soil ions and groundwater, cultivated and fallow soils in the Hetao lrrigation District were analyzed, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In the study by Zou, the maximum rooting depth of maize roots at the grain filling stage was 100 cm, whereas the maximum rooting depth was limited to the depth of the sand layer in the present study. Generally, roots increase their surface area to absorb water and nutrients to meet the normal growth needs of crops [58][59][60][61]. In this study, we found that RL in the horizontal and vertical directions was significantly correlated with yield and WUE, with the highest correlation observed in NR20.…”
Section: Discussionmentioning
confidence: 51%
“…In the study by Zou, the maximum rooting depth of maize roots at the grain filling stage was 100 cm, whereas the maximum rooting depth was limited to the depth of the sand layer in the present study. Generally, roots increase their surface area to absorb water and nutrients to meet the normal growth needs of crops [58][59][60][61]. In this study, we found that RL in the horizontal and vertical directions was significantly correlated with yield and WUE, with the highest correlation observed in NR20.…”
Section: Discussionmentioning
confidence: 51%
“…Under the assumption that temperature, humidity, and wind speed are all equal, solar radiation increased the evaporation intensity. The increased evapotranspiration intensity and the lower water content of the soil increased the water uptake initiative of the yellow willow on the sunny side and exacerbated water demand on the sunny side [37,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on the ion concentration changes in the Yellow River water over an extended period, it is possible to predict and analyze the changes in water salt in the HID in the future when the salt ion composition of the irrigation water changes. Second, the effects of irrigation with brackish water on the soil environment in the HID have already been studied by academics [27,[46][47][48], which can alleviate the risk of the secondary salinization of the soil to a certain extent. Accordingly, the SWAT-Salt model can consider the spatial distribution of saline water in the HID, the amount of extracted water, water quality, and other factors to further explore the impact of combined saline and freshwater irrigation on salt recharge and drainage balance in the HID at the watershed scale.…”
Section: Model Performancementioning
confidence: 99%